INNOVATION OF BUILDING DESIGN BASED ON PREDICTED MEAN VOTE (PMV) INDEX FOR INCREASING HUMAN COMFORT - Sugiono Sugiono (Dimensi: Journal of Architecture and Built Environment, 2016)
Concerning towards the quality of air comfort and safety to pedestrians in the University area should be increased as Indonesia economics booming. The objective of this study is to investigate and then to evaluate the distribution of thermal comfort at the University of Brawijaya, Malang. The research is started with study literature and early survey to collect all information of building layout and building shape at the University of Brawijaya. The information is used to create a 3D model in CAD software. The model is simulated to measure the PMV factors of air temperature, relative humidity and air speed in some locations. The two scenarios of maintaining the predicted mean vote (PMV) is presented by designing the new building based on air foil shape dimension to keep the wind speed in higher value for pedestrian and by putting the water pool in front of the building to increase the air temperature. As a result, the air foil based design is capable to reduce PMV index in average 0.4 scale and pool design is only reducing PMV index level in 0.001 scale